Beyond the cut: a cross-sectional analysis of the long-term clinical and functional impact of cesarean section scars - Laila Lídia Faria Almeida; Gabriel Lage Neves; Matheus Eduardo Soares Pinhati; Rivia Mara Lamaita; Eduardo Batista Cândido; Agnaldo Lopes da Silva Filho (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: This study aims to evaluate the clinical and functional implications of cesarean section (CS) skin scars on women's lives, emphasizing the relationship between scar characteristics and quality of life. Methods: In this cross-sectional study, women older than 18 years old who had undergone CS with a Pfannenstiel incision within the past 6-36 months were evaluated. The Patient Scar Assessment Questionnaire (PSAQ) and the Patient and Observer Scar Assessment Scale (POSAS) were used to assess clinical scar parameters. Functionality was appraised using eight questions derived from the International Classification of Functionality, Disability, and Health (ICF). The association between scar appearance scores and functionality questions was analyzed statistically. Results: Ninety-six women were assessed, revealing that appearance and satisfaction with appearance had the worst scores on the PSAQ. Scar irregularity was the most frequently reported scar characteristic on the POSAS. On the ICF-derived questionnaire, the "self-care" domain was the most affected, with women reporting problems on activities such as choosing swimwear and lingeries. There was a significant correlation (p < 0,05) between the women dissatisfaction with the scar appearance and impairment in ‘interpersonal interactions and relationships’ and ‘self-care’, as the "domestic life" domain wasn't affected. Conclusions: Cesarean section skin scars can lead to dissatisfaction and functional impairments, affecting women's quality of life. These findings underscore the necessity for multidisciplinary care and thorough discussions about delivery methods to improve post-surgical outcomes.